2015
DOI: 10.1515/gospo-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Rtęć w odpadach z procesu wzbogacania węgli kamiennych

Abstract: Streszczenie Rtęć dość powszechnie występuje zarówno w węglu brunatnym, jak i kamiennym. Uważa się, że w substancji mineralnej węgla powiązana jest ona głównie z pirytem, a w substancji organicznej z grupami tiolowymi. Niemniej jednak spotykane są również węgle, w których rtęć w znacznych ilościach powiązana jest z węglanami i krzemianami. Można by zatem oczekiwać, że ilość występującej w węglu rtęci powinna być skorelowana z zawartością substancji mineralnej czy zawartością popiołu. Jednak w literaturze infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…the obtained results and analyses clearly indicate a strong dependence of occurrence of mercury and total sulfur in the material. Similar conclusions were obtained for the coexistence of these elements in the paper by t. Dziok et al (2015). the results presented in that paper indicate the presence of mercury in pyrite in the waste material (Dziok et al 2015).…”
Section: Study Of Mercury Content In the Individual Grain Size Fractisupporting
confidence: 87%
See 2 more Smart Citations
“…the obtained results and analyses clearly indicate a strong dependence of occurrence of mercury and total sulfur in the material. Similar conclusions were obtained for the coexistence of these elements in the paper by t. Dziok et al (2015). the results presented in that paper indicate the presence of mercury in pyrite in the waste material (Dziok et al 2015).…”
Section: Study Of Mercury Content In the Individual Grain Size Fractisupporting
confidence: 87%
“…Studies in the literature on mercury content in extractive waste are less numerous. Values are given for the extractive wastes from the UScB (table 1) range between 0.006 and 0.380 mg/kg, with an average value of 0.087 mg/kg (Michalska and Białecka 2012;Bzowski and Dawidowski 2013;Dziok et al 2015;Klojzy-Karczmarczyk et al 2016a;Klojzy-Karczmarczyk et al 2016d;Wichliński et al 2016). Mercury in coals (and thus in waste) can be bound to both organic and mineral substances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of coal combustion, a number of pollutants can be created due to the presence of polluting components in coal (e.g. Klojzy-Karczmarczyk and Mazurek 2013;Dziok et al 2015;Klojzy-Karczmarczyk et al 2016a, 2016bKosa and Kicinska 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The existing results of research have revealed that cleaning of Polish hard steam coal enables to reduce the mercury content in clean coal, in comparison with raw coal, by 18-79 % [10][11][12]. More detailed research showed that the result of coal cleaning, in terms of the mercury content reduction, depended on technological characteristics of given coal and on the size fraction of cleaned coal [12].…”
Section: Introductionmentioning
confidence: 99%